Fever pitch: Coloniality and contention within community health’s yellow fever response in Kenya - Kathy Dodworth; Brenda N. Mukungu (Global Public Health)
In January 2022, a number of Yellow Fever cases were identified in Kenya’s Isiolo County for the first time, triggering a national-level response centred on vaccinating residents. 181,000 people were vaccinated in July, around 72% of the eligible population. In the face of this ostensible success, this article explores the continuing coloniality, that is, long-standing patterns of domination, operating within disease control in Kenya’s northeast, whereby punitive encounters with the state loom large. Despite health matters being devolved, top-down implementation from nationally-controlled actors exacerbated local distrust, resulting in contention around the roll-out and of the authorities behind it. This article, drawing on ethnography supplemented by in-depth interviews and Focus Group Discussions over 12 months 2022-2023, centres the experiences of Community Health Volunteers (CHVs) over the ten-day campaign. We adopt a Fanonian lens to interpret our findings, historicizing the contention CHVs faced from their communities, in a region where governmental approaches oscillate between neglect and heavy-handed remedial action. We operationalise Fanon’s ‘psychoexistential complex’, whereby CHVs internalise the conflict between their roles of community representative and state-enforcer, exacerbated by their precarity and invisibility to others. We conclude with a call for CHVs’ place to be protected, capacitated and seen within outbreak response.